The contributions of working memory and pre-task explicit instruction to L2 oral performance. (February 2021) - Sadeghi, Michael; Pourhaji, Mostafa
Abstract: This study investigates to what extent working memory (WM) and explicit instruction in the pre-task stage predict the quality of L2 oral performance on a focused task. The WM of 103 Iranian low-proficiency learners of English was measured using an operation span task. Then, they were randomly assigned to an experimental and a control group. Both groups performed a focused story-retelling task designed to elicit English relative clauses. Prior to task performance, they both had 5 min of planning time, yet the experimental group also received explicit instruction during that time span. The results indicated that explicit instruction is a negative predictor of fluent speech with positive contributions to global complexity and the rate and accuracy of relativization. Moreover, WM was found to be a positive predictor of global complexity and fluency together with accurate and frequent relativization. The findings provide pieces of evidence towards revisiting the dispute over the desirability of drawing learners' attention to specific linguistic forms before task performance. The positive and strong contributions of WM raise awareness about the possibility that learners may treat tasks differently due to their individual differences.